Influence of Green Accounting, Company Size, Leverage, And Profitability on Return On Asset (ROA) of Mining Companies - Nadiyah, Farah Ashma; Fanani, Baihaqi; Susetyo, Budi (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study aims to examine the influence of green accounting, company size, leverage (DER), and profitability (NPM) on return oon asset (ROA) of mining companies during the 2019–2024 period. Methodology: This research uses a descriptive quantitative approach with multiple linear regression analysis. A total of 275 observations were analyzed using SPSS Statistics 25 as the data processing tool. Results: The results show that green accounting and company size have a significant positive effect on ROA. Meanwhile, DER and NPM have no significant effect on ROA. The coefficient of determination (R²) is 16.7%, indicating that the independent variables explain 16.7% of the variation in ROA. Findings: The main finding highlights the importance of green accounting and company scale in improving ROA. Novelty: This study introduces a novelty by combining green accounting, firm size, leverage, and profitability to examine ROA over the post-pandemic period (2019–2024). Originality: The originality lies in the independently constructed conceptual framework and the integration of stakeholder and legitimacy theory in interpreting the findings. Conclusion: Implementing green accounting and increasing company size can enhance financial performance as measured by ROA. Type of Paper: Empirical Research.